Dissecting the role of lipocalin in Plasmodium falciparum - Baptista, Vitória Cunha (2023)
[Excerpt] Malaria, caused by Plasmodium parasites, is an infectious disease responsible for millions of cases and deaths yearly. Despite the efforts, the disease control has been continuedly threatened by the resilient capacity of the parasite to acquire resistance to antimalarial drugs treatment, which target the symptomatic intraerythrocytic developmental cycle.